Teacher's Difficulties in Teaching Reading Skills in Exposition Text at SMAN 1 Percut Sei Tuan - Yohana Simanjuntak; Yohana Simanjuntak; Ameera Fadhillah; Annisa Salsabila (Universitas Negeri Medan, 2026)
This study explores the teacher's difficulties in teaching reading skills in exposition texts at SMAN 1 Percut Sei Tuan. The research focuses on identifying the challenges faced by the teacher in teaching students' reading skills. Through a qualitative analysis, the studies identifies that the teacher encountered several difficulties is related to the students' limited vocabulary, lack of students' reading comprehension, pronunciation, students' reading interest, and provide the variety of reading materials. The students' ability to read aloud the text clearly is still low. Mispronunciation words and their interest in reading exposition text were reflected in their unenthusiastic participation during classroom reading activities and their lack of initiative in answering the teacher's question while reading the text. Furthermore, the findings highlight that these difficulties affected to the teaching and learning process into stiff and less enjoyable classroom atmosphere. It make the teacher often repeatedly explain the text and guide the students just to read it properly. Despite of that difficulties, the overall result emphasize that the importance ability of the teacher to manage on how the exposition text is understandable and suitable for the students' english level is important to adapt for the effective teaching reading skills. The study concludes that the difficulties are interconnected and influenced by students' ability, motivation and classroom engagement.